Using Importance Performance Analysis to Evaluate the Satisfaction of Activity-Based Costing Adopters - Karim Charaf; Ahmed Fath-Allah Rahmouni (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This paper examines the satisfaction of the users of Activity-Based Costing (ABC) of Moroccan companies. Relying on the Importance Performance Analysis (IPA) tool, we attempt to analyze the importance and the performance that ABC uses to identify strengths and weaknesses; and therefore, develop a possible method to improve different applications. Using the survey method, two types of companies were studied: Activity Based costing (ABC) adopters and non-ABC adopters. The results suggest that the ABC adopters were more efficient and more satisfied with their cost system. However, they did not fully benefit from the contributions of the ABC system. Some uses such as budgeting, outsourcing decisions and customer quotes were low. In general, Moroccan companies should put more effort into improving the use of their costing system. This research contributes to explaining how companies can use IPA to analyze their ABC systems to improve resource allocation and for better decision-making.
Keywords: M41; 650; Activity-Based Costing/Management; Importance Performance Analysis; Cost information; Moroccan Companies